PATHOLOGICAL ANATOMY AS THE FOUNDATION OF MEDICAL THINKING: FROM MORPHOLOGICAL ARCHIVE TO CLINICAL DECISION-MAKING IN THE EDUCATIONAL PROCESS AT GIDUVа - Bondarev, Oleg Ivanovich; Razvozhaev, Yury Borisovich (Medicine in Kuzbass, 2026)
The article highlights the pivotal role of pathological anatomy in developing clinico-morphological reasoning, intellectual maturity, and ethical worldview among physicians within continuing medical education. Using the educational model of the Novokuznetsk State Institute for Physicians’ Improvement (GIDUV) as an example, it demonstrates how a unique morphological archive, decades of scientific expertise, and the close integration of faculty with clinical practice foster deep disciplinary understanding.Special attention is given to the legacy of distinguished department heads – N.F. Kan’shina, V.A. Rykov, and B.P. Darovsky – whose pioneering work laid the foundations for the study of renal failure and iatrogenic pathology.The article also emphasizes the enduring influence of classical Russian pathologists – N.I. Pirogov, A.I. Abrikosov, V.F. Voyno-Yasenetsky, I.V. Davydovsky – whose ideas continue to shape the pedagogical philosophy of the department and cultivate logical analysis, scientific reflection, and responsible clinical judgment in learners.
Keywords: pathological anatomy; medical education; GIDUV; clinico-morphological reasoning; morphological archive; physician competency development; I.V. Davydovsky; V.F. Voyno-Yasenetsky; A.I. Abrikosov; N.F. Kan’shina; V.A. Rykov; B.P. Darovsky